The Effect of Early Childhood Language Training Programs on the Contemporary Formation of Grammar Skills - Daniel Kamhöfer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
While there is a big literature on the benefits of pre-school education, only little is known why kindergarten attendance improves later-life outcomes. This is partly because most studies analyze the effect of complete 2 years pre-school programs. In order to shed light into the black box of kindergarten education, I am using the German National Educational Panel Study and regress the level of grammar skills - a main intelligence component - on the participation in a nationwide-used language training program and a rich set of conditioning variables. Taking information on mathematical skills into account, this paper also employs matching and differences-in-differences methods as well as a combination of both. The estimated effects of participating in a language training program at the kindergarten on grammar skills range between 11% and 17% of a standard deviation.
Keywords: I21; I28; J24; 330